2003
DOI: 10.4049/jimmunol.171.11.6119
|View full text |Cite
|
Sign up to set email alerts
|

FcεRI Signaling of Mast Cells Activates Intracellular Production of Hydrogen Peroxide: Role in the Regulation of Calcium Signals

Abstract: Earlier studies, including our own, revealed that activation of mast cells is accompanied by production of reactive oxygen species (ROS) that help to mediate the release of the inflammatory mediators, including histamine and eicosanoids. However, little is known about the mechanisms of ROS production, including the species of oxidants produced. In this study we show that in both the RBL-2H3 mast cell line and bone marrow-derived mast cells, FcεRI cross-linking stimulates intracellular oxidative burst, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 47 publications
8
109
1
2
Order By: Relevance
“…These data suggest that Nox1 acts downstream of ROS generation in Ag-stimulated mast cells, thus mediating the synthesis of Th2 cytokines. Consistent with our observation, DPI-sensitive flavoenzymes such as Nox were previously suggested to be involved in Ag-mediated ROS production in mast cells (44,45). We found that transient transfection with a BLT2 expression plasmid alone caused a modest increase in Nox1 transcript levels, ROS generation, and Th2 cytokine synthesis and that the addition of BLT2 ligands further increased these effects (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…These data suggest that Nox1 acts downstream of ROS generation in Ag-stimulated mast cells, thus mediating the synthesis of Th2 cytokines. Consistent with our observation, DPI-sensitive flavoenzymes such as Nox were previously suggested to be involved in Ag-mediated ROS production in mast cells (44,45). We found that transient transfection with a BLT2 expression plasmid alone caused a modest increase in Nox1 transcript levels, ROS generation, and Th2 cytokine synthesis and that the addition of BLT2 ligands further increased these effects (Figs.…”
Section: Discussionsupporting
confidence: 78%
“…Compound 48/80 has been shown to penetrate cellular membranes and directly activate G proteins. This activation involves insertion of an aromatic ring of Compound 48/80 into the membrane and interaction of a positively-charged domain of the molecule with the COOH-terminal portion of the α-subunit of G protein (Fukuishi et al, 1997;Brooks et al, 1999;Suzuki et al, 2003). In the in vitro studies performed here, EAFAS attenuated the rate of mast cell degranulation in a dose-related manner as observed microscopically by toluidine blue staining.…”
Section: Discussionmentioning
confidence: 72%
“…Imaging of intracellular Ca 2+ fluxes was performed as previously described (Suzuki et al, 2003). Briefly, RBL-2H3 cells (5 × 10 4 ) were plated in the wells of chamber slides (Nalge Nunc Int, Naperville, IL) and cultured for 2 days.…”
Section: Assessing the Change In Intracellular Ca 2+ Content By Confomentioning
confidence: 99%